2022
DOI: 10.3390/molecules27238145
|View full text |Cite
|
Sign up to set email alerts
|

Edible Mushrooms as Source of Fibrin(ogen)olytic Enzymes: Comparison between Four Cultivated Species

Abstract: Cardiovascular diseases represent the main cause of death. A common feature of cardiovascular disease is thrombosis resulting from intravascular accumulation of fibrin. In the last years, several fibrinolytic enzymes have been discovered in many medicinal or edible mushrooms as potential new antithrombotic agents. This study aimed to compare the fibrin(ogen)olytic activity of crude extracts from the fruiting bodies of four cultivated edible mushrooms: Lentinula edodes, Pleurotus ostreatus, Pleurotus eryngii, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
5
0
1
Order By: Relevance
“…The enzyme exhibited favorable stability within the pH range of 6.6 to 8.2 for 6 h. In this stable pH range, the enzyme activity remained above 80% after 4 h of incubation and still exceeded 71.2% after 6 h. However, following a 24 h incubation period, the residual enzyme activity was observed to be greater than 60.2% (Figure 4D). As already reported, the optimal pH for mushroom fibrinolytic enzymes was within a pH range of 4 to 9, although most of them had an optimal pH between 7 and 7.8 [14,16,[29][30][31][32][33][34][35]. Fibrinolytic enzymes, such as those from Neurospora sitophila [36] and Pleurotus ostreatus [14], showed similar results with an optimal pH value of 7.4.…”
Section: Effects Of Temperature and Ph On The Activity Of Cfesupporting
confidence: 76%
See 1 more Smart Citation
“…The enzyme exhibited favorable stability within the pH range of 6.6 to 8.2 for 6 h. In this stable pH range, the enzyme activity remained above 80% after 4 h of incubation and still exceeded 71.2% after 6 h. However, following a 24 h incubation period, the residual enzyme activity was observed to be greater than 60.2% (Figure 4D). As already reported, the optimal pH for mushroom fibrinolytic enzymes was within a pH range of 4 to 9, although most of them had an optimal pH between 7 and 7.8 [14,16,[29][30][31][32][33][34][35]. Fibrinolytic enzymes, such as those from Neurospora sitophila [36] and Pleurotus ostreatus [14], showed similar results with an optimal pH value of 7.4.…”
Section: Effects Of Temperature and Ph On The Activity Of Cfesupporting
confidence: 76%
“…Even after a prolonged incubation period of 4 h at these temperatures, the enzyme maintained an activity level exceeding 71.32% (Figure 4B). However, the relative enzyme activity and thermal stability of the enzyme decreased significantly when the temperature exceeded 47 • C. Optimal temperatures for the majority of fibrinolytic enzymes derived from mushrooms typically fall within the temperature range of 20 • C to 60 • C [29][30][31][32][33][34][35]. The optimal temperature of CFE was similar to that of the fibrinolytic enzymes from Bacillus amyloliquefaciens GUTU06 [32] and Coprinopsis atramentaria [33], which exhibited optimal temperatures of 45 • C and 50 • C, respectively.…”
Section: Effects Of Temperature and Ph On The Activity Of Cfementioning
confidence: 87%
“…Tania et al compared the antithrombotic effects of four types of mushrooms ( Lentinula edodes , Pleurotus ostreatus , Pleurotus eryngii , and Agrocybe aegerita ) but presented only fibrin(ogen)olytic results [ 44 ]. Xiao et al only revealed the physicochemical characteristics of thrombolytic enzymes, indicating limitations in the potential development of mushroom-derived antithrombotic materials [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, they have a low lipid content and a high content of proteins, fibres, unsaturated fatty acids, glucans, vitamins, phenolic compounds, minerals, and secondary metabolites [51,[56][57][58]. Numerous studies have shown that edible mushrooms possess anticancer, antiatherosclerotic, hypocholesterolemic, hypolipidemic, antiviral, antimicrobial, immunostimulant, anti-inflammatory, antioxidant, fibrinolytic, and anti-aging properties [11,[59][60][61][62][63][64][65][66]. Furthermore, edible and medicinal mushrooms contain several mycochemicals with antioxidant activity, such as phenols, flavonoids, polysaccharides, vitamins, carotenoids, ergothioneine, and others [57,[67][68][69] (Figure 2).…”
Section: Mushrooms As Sources Of Antioxidant Compoundsmentioning
confidence: 99%